Strategies utilized in a search for new drugs active against blood neoplasia - Wiktor Jędrzejczak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2001)
In a search for drugs active against cancer, medicine is exploring all possibilities. Currently they include: testing all newly discovered or synthetized compounds for their activity against neoplasia, reevaluation of known drugs for unknown or underestimated activities, selection and design of novel compounds utilising knowledge concerning mechanisms of carcinogenesis, utilisation of antibodies recognising surface structures of neoplastic cells and elaboration of new, better forms of already acknowledged drugs. All this creates the situation in which in the treatment of blood neoplasia we have more and more therapeutic options for steadily increasing price.